Productivity and profitability of coriander varieties influence by sowing times and plant growth regulators - Kuri, B.R.; Jat, N.L.; Shivran, A.C.; Puniya, M.M. (Annals of Agricultural Research, 2016)
A field experiment was conducted for two consecutive rabi seasons of 2011-12 and 2012-13 at Agronomy Farm, S.K.N. College of Agriculture, Jobner (Rajasthan), to study the effect of sowing times and plant growth regulators on productivity and profitability of coriander varieties grown on irrigated loamy sand soil of semi-arid eastern plain zone of Rajasthan. The experiment was carried out in split plot design with two sowing times (normal and late sown) and three varieties (RCr-41, RCr-435 and RCr-480) in main plots and five plant growth regulators (control, triacontanol @ 1000 ppm, brassinolide @ 1 ppm, thiourea @ 1000 ppm and NAA @ 50 ppm at 40 and 70 DAS) in sub plots. The results revealed that the normal sown crop produced significantly higher yield attributes viz. number of umbels/plant, umbellets/umbel, seeds/umbel and test weight and gave higher seed (1.48 t/ha), stover and biological yields, net returns (Rs 32,810/ha) and B:C (1.25) ratio as compared to late sown. Among, these varieties RCr-480 produced significantly higher yield attributes, yields, net returns and B:C ratio as compared to RCr-41 and RCr-435, while it remained at par with RCr435 in yield attributes and yields. The results further revealed that foliar application of 1000 ppm triacontanol significantly increased yield attributes, seed (1.40 t/ha), stover and biological yields, net returns (Rs 30,020/ha) and B:C (1.15) ratio over control, 50 ppm NAA, 1000 ppm thiourea and 1 ppm brassinolide but remained at par with brassinolide in yield attributes and yields on pooled basis.